Potential of Curcumin in Curcuma Longa as an Alternative Therapy for PCOS: A Literature Review - Ishlahi, Salsabila Dinda Nuril; Octora, Metta (Jurnal Biologi Tropis, 2024)
Polycystic ovary syndrome (PCOS) is a common reproductive endocrine hormone disorder in women of childbearing age with a global incidence of 8-13%. The use of medical drugs in the long term can cause serious side effects so that the utilization of curcumin contained in Curcuma longa can be an alternative therapy consideration for PCOS. This paper will discuss the potential and benefits of curcumin content as an alternative therapy for PCOS. The method used, namely by reviewing the literature in national and international journals that are in accordance with the objectives of the review. The results of the literature review show that curcumin has effectiveness in treating PCOS through various mechanisms of action accompanied by minimal side effects. Alternative therapy of PCOS by taking curcumin needs to consider the dose, duration of use, and further research with larger subjects in assessing its effectiveness and side effects. However, it is suspected that nanocurcumin formulations have higher bioavailability and solubility than free curcumin, giving it even greater potential in the treatment of PCOS in the future. In conclusion, curcumin has the potential as an alternative therapy for PCOS that requires further research to achieve the optimization of PCOS treatment in the future.